2003
DOI: 10.1248/bpb.26.409
|View full text |Cite
|
Sign up to set email alerts
|

Two Regions Responsible for the Actin Binding of p57, a Mammalian Coronin Family Actin-Binding Protein.

Abstract: The actin-binding protein p57, a member of the coronin protein family, is expressed in a variety of immune cells. It has five WD repeats and a coiled-coil motif containing a leucine zipper, both of which are known to mediate protein-protein interactions. In order to identify the precise actin-binding regions in p57, and to assess the contribution of these structural motifs, we prepared various truncated p57 as fusion proteins with glutathione S-transferase (GST) and examined their actin-binding activity. A co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 32 publications
5
52
1
1
Order By: Relevance
“…Other F-actin binding proteins, such as N-WASP, Btk, and p57 have been shown to possess basic and hydrophobic amino acid-enriched regions that interact with corresponding acidic amino acid clusters on actin (19,22,27). Consistent with this, we found that SPIN90 contains a highly hydrophobic and basic region at the end of its C-term (582-722).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Other F-actin binding proteins, such as N-WASP, Btk, and p57 have been shown to possess basic and hydrophobic amino acid-enriched regions that interact with corresponding acidic amino acid clusters on actin (19,22,27). Consistent with this, we found that SPIN90 contains a highly hydrophobic and basic region at the end of its C-term (582-722).…”
Section: Discussionsupporting
confidence: 81%
“…Our results revealed that GST alone and GST-C-term (269-656) failed to co-sediment with Factin, whereas GST-C-terminus (269-722) and GST-C-term (657-722) both bound F-actin ( Figure 2B). These results suggest that the region responsible for SPIN90 binding to F-actin is located at the SPIN90-C-term (657-722), implicating that the basic and hydrophobic amino acids are essential for F-actin binding of SPIN90 (11,19,22,27). When we estimated the dissociation constant (K d ) for a SPIN90-full, -Cterminus (269-722) and -C-term (657-722) with respect to F-actin, we found that the association of the GST-SPIN90-full, -C-terminus (269-722), and -Cterm (657-722) with F-actin became saturated as the F-actin concentration increased.…”
Section: Spin90-c-term (657-722) Is Required For F-actin Bindingmentioning
confidence: 90%
See 1 more Smart Citation
“…Coronin 1b is an actin-binding protein, belonging to the Coronin family, and may bind also to tubulin (27). It is important in cytoskeleton remodeling, lamellipodia extensions and mitosis; moreover, Coronin 1b is localized to the cortical cytoskeleton, where it is co-localized with F-actin (36,37). It is known that cytoskeletal organization and remodeling are essential cellular modifications during sprouting and axonal elongation (for review, see Ref.…”
Section: Coronin 1b and Rab13 Protein Expression Is Induced After Scmentioning
confidence: 99%
“…A previous study suggested that two regions within N-terminal and central part of p57 (Met-1 to Asp-34 and Ile-111 to Glu-204) are responsible for actin binding [12]. However, it has been reported that the deletion of the C-terminal 65 amino acids from Xcoronin, a Xenopus homologue of coronin, significantly reduces its actin-binding activity [13].…”
Section: Introductionmentioning
confidence: 99%